Goat Farm Management Application at Golden Star Farm Based on Android - Romadhon, Nur Aditya; Ardiani, Farida (ILKOMNIKA, 2025)
This study designs and implements an Android-based goat farm management application at Golden Star Farm, Cilacap. The main issues addressed are the disorganized sales data recording and the lack of socialization regarding goat care procedures among employees. The system was developed using the Rapid Application Development (RAD) method to ensure speed and accuracy in meeting user needs. This application improves the accuracy of sales data recording, facilitates access to goat care information, and provides a user authentication system. Testing using the Black Box Testing method shows that all features function properly. The research results prove that this application reduces errors in data recording, enhances employee understanding of goat care, and positively impacts livestock health and the sustainability of the farming business.